2021
DOI: 10.21037/atm-21-5701
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β activates NF-κB to aggravate caerulein-induced early acute pancreatitis in mice

Abstract: Background: Acute pancreatitis is a life-threatening disease which causes considerable morbidity and mortality. However, no specific and effective treatments are currently available for this critical condition, which is mainly due to the insufficient understanding of the early cellular events in the initial phase of acute pancreatitis. Previous researchers have reported that two independent events, intra-acinar trypsinogen and NF-κB activation, are of equal importance in the early development of acute pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…GSK‐3β activation promotes proinflammatory response (Fu et al, 2021) and invokes oxidative damage (Wang et al, 2009) and its activation depends on the phosphorylation at Tyr216. The intensity and expression level of spinal pGSK‐3β‐Tyr216 was greatly increased in OXA group with intensity value at 2.00 ± 0.17 (Figure 4d,e) and gray value at 2.02 ± 0.21 (Figure 4f,g).…”
Section: Resultsmentioning
confidence: 99%
“…GSK‐3β activation promotes proinflammatory response (Fu et al, 2021) and invokes oxidative damage (Wang et al, 2009) and its activation depends on the phosphorylation at Tyr216. The intensity and expression level of spinal pGSK‐3β‐Tyr216 was greatly increased in OXA group with intensity value at 2.00 ± 0.17 (Figure 4d,e) and gray value at 2.02 ± 0.21 (Figure 4f,g).…”
Section: Resultsmentioning
confidence: 99%
“…GSK-3β dysregulation was crucial in the pathogenesis of inflammatory diseases, including diabetic wound-healing [ 35 ], and was found to regulate the inflammatory response via Wnt/β-catenin/NF-κB axis [ 36 ]. It was reported that GSK-3β inhibited Wnt/β-catenin signaling pathway [ 37 ], while activating NF-κB [ 38 ]. Moreover, silencing β-catenin promoted the expression of NF-κB [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, after knocking down LRFN2, the expression of NF‐κB and BCL2 increased. Studies have shown that GSK3B can stimulate the NF‐κB pathway, 37 , 38 , 39 so we hypothesized whether LRFN2 could affect the NF‐κB pathway due to changes in p ‐GSK3B (SER389), thereby affecting the occurrence of ESCC. This means that LRFN2 affects both the WNT and NF‐κB signaling pathways through GRIN2B, and the key molecule is GSK3β.…”
Section: Discussionmentioning
confidence: 99%